Early detection of breast and cervical cancer among indigenous communities in Morelos, Mexico. - Lourdes Campero; Erika E Atienzo; Eréndira Marín; Elvia de la Vara-Salazar; Blanca Pelcastre-Villafuerte; Guillermo González (Instituto Nacional de Salud Pública, 2014)
Objective. To analyze the perception in relation to when and how to perform actions for the early detection of breast and cervical cancer among women and health care providers in communities with a high percentage of indigenous population in Morelos, Mexico. Materials and methods. Ten health providers and 58 women users of health services were interviewed which have a first level of attention in five communities. The analysis was developed under the approach of the Grounded Theory. Results. Providers are poorly informed about current regulations and specific clinical indications for the detection of cervical and breast cancer. Few propitiate health literacy under intercultural sensitization. The users have imprecise or wrong notions of the early detection. Conclusions. The need for training in adherence to norms is evident. It is urgent to assume a culturally relevant approach to enable efficient communication and promote health literacy for early detection of these two cancers.